Use of partial melting in Tl-1223 coil production - Moore, J; Eastell, C; Naylor, M; Hyland, D; Fox, S; Boffa, V; Bruzzese, R; Grovenor, C; Goringe, M (Minerals, Metals and Materials Soc (TMS), 1996)
We report progress towards defining the optimum conditions for melt processing TlBi-1223 PIT tapes. The Bi substitution level has been found to have a strong influence on these conditions, affect the intercalation structure of the 1223 phase and the amount of secondary phases observed. TEM studies have identified a new Ba-Sr-Bi-Ca-O phase with a layered structure. A 3 pancake coil of length greater than 10m has been fabricated and tested in high magnetic fields. We conclude that although melt processing can be used to significantly modify the grain structure, further work on grain alignment is required to achieve useful properties.